1993
DOI: 10.1037/0735-7044.107.1.3
|View full text |Cite
|
Sign up to set email alerts
|

A triple dissociation of memory systems: Hippocampus, amygdala, and dorsal striatum.

Abstract: This study investigated the respective roles of the hippocampus, the amygdala, and the dorsal striatum in learning and memory. A standard set of experimental conditions for studying the effects of lesions to the three brain areas using an 8-arm radial maze was used: a win-shift version, a conditioned cue preference (CCP) version, and a win-stay version. Damage to the hippocampal system impaired acquisition of the win-shift task but not the CCP or win-stay tasks. Damage to the lateral amygdala impaired acquisit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

49
650
5
3

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 996 publications
(707 citation statements)
references
References 141 publications
(254 reference statements)
49
650
5
3
Order By: Relevance
“…If this is the case, then an important functional distinction between subsystems within the amygdala complex might be possible. In contrast to our results, McDonald and White (6) found that damage to the lateral nucleus of the amygdala abolished the acquisition of learned cue preferences in rats. The basolateral nucleus of the amygdala has also been implicated in the acquisition of cue value (8).…”
Section: The Role Of the Amygdala Central Nucleus (Cn) In Associativecontrasting
confidence: 55%
See 1 more Smart Citation
“…If this is the case, then an important functional distinction between subsystems within the amygdala complex might be possible. In contrast to our results, McDonald and White (6) found that damage to the lateral nucleus of the amygdala abolished the acquisition of learned cue preferences in rats. The basolateral nucleus of the amygdala has also been implicated in the acquisition of cue value (8).…”
Section: The Role Of the Amygdala Central Nucleus (Cn) In Associativecontrasting
confidence: 55%
“…In one commonly employed task, rats normally learn to seek, or remain in, an environment associated with reward, a phenomenon referred to as conditioned place preference. Rats with amygdala damage fail to show this form of associative learning (6). In the past decade, the study of acquired emotional responses has yielded much information about the neural circuits in the amygdala that are involved in associative learning.…”
Section: The Role Of the Amygdala Central Nucleus (Cn) In Associativementioning
confidence: 99%
“…The striatum, which is significantly larger in video game players (VGPs) [11,12], shares an inverse relationship with the hippocampus [16,19]. In contrast to the striatum's critical role in response learning and memory, and habit formation by making rigid stimulus-response associations [15,[20][21][22][23], the hippocampus is critical for allocentric spatial learning and memory, and the formation of a cognitive map (i.e. learning and memory for the relationships between environmental landmarks) irrespective of the position of the observer [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…riding a bicycle) [14]. The striatum also plays a role in stimulus-response learning, which involves making a particular action when faced with an environmental trigger that acts as a stimulus [15,16]. Increased striatal volume and activity are also associated with decreased volume and activity in the hippocampus [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Work with animal models (McDonald & White, 1993;Packard & McGaugh, 1996), patient H.M. (Scoville & Milner, 1957), and other amnesic patients (Cohen & Squire, 1980;Knowlton et al, 1996) is suggestive of a dissociation between memory of cognitive and motor skills such as mirror drawing and memory of facts or episodes (Eichenbaum & Cohen, 2001;Squire & Dede, 2015). From these studies, researchers have concluded that skill knowledge is supported by a different system from that which supports factual or episodic knowledge, with skill knowledge being supported by procedural memory and factual/episodic knowledge by declarative memory.…”
Section: Declarative and Procedural Memory In L2 Aptitudementioning
confidence: 95%